Can I Ask a Question About URiM Awards That I Don't Know the Answer to? Designing an Award for Underrepresented Medical Education Researchers. (9th August 2022) - Zaidi, Zareen; Sewell, Justin L.; Schumacher, Daniel; Sukhera, Javeed; Hunderfund, Andrea N. Leep; Balmer, Dorene F.; Park, Yoon Soo; Kulasegaram, Kulamakan; Young, Meredith E.; Fung, Cha-Chi; LaDonna, Kori A.
Abstract : Meaningful Equity, Diversity, and Inclusion (EDI) efforts may be stymied by concerns about whether proposed initiatives are performative or tokenistic. The purpose of this project was to analyze discussions by the Research in Medical Education (RIME) Program Planning committee about how best to recognize and support underrepresented in medicine (URiM) researchers in medical education to generate lessons learned that might inform local, national, and international actions to implement meaningful EDI initiatives. Ten RIME Program Planning Committee members and administrative staff participated in a focus group held virtually in August 2021. Focus group questions elicited opinions about "if and how" to establish a URiM research award. The focus group was recorded, transcribed, and thematically analyzed. Recognition of privilege, including who has it and who doesn't, underpinned the focus group discussion, which revolved around 2 themes: (1) tensions between optics and semantics, and (2) potential unintended consequences of trying to level the medical education playing field. The overarching storyline threaded throughout the focus group discussion was intentionality. Focus group participants sought to avoid performativity by creating an award that would be meaningful to recipients and to career gatekeepers such as department chairs and promotion and tenure committees. Ultimately, participants decided to create an award that focused on exemplary Equity, Diversity, and Inclusion (EDI) scholarship, which was eventually named the "RIME URiM Research Award." Difficult but productive conversations about EDI initiatives are necessary to advance underrepresented in medicine (URiM) scholarship. This transparent commentary may trigger further critical conversations.